MINERAL ANALYSIS (CU, PB AND CD) AND BIO-PHYSICAL CHEMISTRY TEST HONEY ORIGIN DISTRICT. KINDANG BULUKUMBA - Rabiatul Adawiah; Alfian Noor; Maming Gaffar (Marina Chimica Acta, 2017)
Honey is a natural product produced by bees that contain nutrients that are very essential. Honey is not only a material sweeteners, flavoring or food, but is also used for drugs. This research aims to know the quality of honey Kindang Bulukumba Subdistrict origin. Mineral content in honey is one of the factors determining the quality of honey, for the analysis of minerals (copper, lead and cadmium) and test of bio-chemical physics with ICP-OES instruments. The concentration of minerals copper, was 0, 024mg/L, while the lead and cadmium was not detected by the value parameter test bio-chemical physics is honey; the grey levels of 0.26%; moisture content 19,69%; DHL 0, 41mS/cm; the acidity of 22, 06meq/kg; pH 4.43; 7.19% protein; fat 0,1301%; 77,55% carbohydrates. The results showed that the original honey Kindang has a quality in accordance with the National standard of Indonesia and the International Honey Commission